2017
DOI: 10.1037/xhp0000293
|View full text |Cite
|
Sign up to set email alerts
|

Does text contrast mediate binocular advantages in reading?

Abstract: Humans typically make use of both of their eyes in reading and efficient processes of binocular vision provide a stable, single percept of the text. Binocular reading also comes with an advantage: reading speed is high and word frequency effects (i.e., faster lexical processing of words that are more often encountered in a language) emerge during fixations, which is not the case for monocular reading (Jainta, Blythe, & Liversedge, 2014). A potential contributor to this benefit is the reduced contrast in monocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 66 publications
5
31
3
Order By: Relevance
“…They found that when English sentences were read with one eye, the processing benefit for high frequency words was eliminated in both gaze duration and fixation times (Jainta et al, 2014, jointly manipulated the preview reading conditions and the target reading conditions-preview benefits are not relevant to our study, so we focus only on the viewing conditions when reading the target words). Jainta et al (2017) observed the same elimination of the frequency effect under monocular reading conditions for gaze duration and first fixation times in German. The total reading time measure continued to show a word frequency effect (one-tailed) under monocular conditions, but it was less than half the magnitude of the effect under binocular conditions (see Figure 1).…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…They found that when English sentences were read with one eye, the processing benefit for high frequency words was eliminated in both gaze duration and fixation times (Jainta et al, 2014, jointly manipulated the preview reading conditions and the target reading conditions-preview benefits are not relevant to our study, so we focus only on the viewing conditions when reading the target words). Jainta et al (2017) observed the same elimination of the frequency effect under monocular reading conditions for gaze duration and first fixation times in German. The total reading time measure continued to show a word frequency effect (one-tailed) under monocular conditions, but it was less than half the magnitude of the effect under binocular conditions (see Figure 1).…”
Section: Introductionsupporting
confidence: 56%
“…Indeed, we are unable to conceive how such models could even show a reduction of the word frequency effect due only to slowing of high frequency items. In short, the results reported by Jainta et al (2014Jainta et al ( , 2017 should they generalize to single word reading experiments, would strongly challenge current thinking about one of the most widely accepted benchmarks used to evaluate accounts of single word reading aloud.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations